(untitled) (JURISMA : Jurnal Riset Bisnis & Manajemen, 2021)
This study aims to determine the community’s acceptance using of the modification Technology Acceptance Model approach for internet television services. The type of research is descriptive and verification with the descriptive survey method. For operational variables consist of perceived usefulness, perceived enjoyment, perceived quality, attitude, and intention. Data obtained from Indonesia for internet television which is amounting to 213 people. The data were collected using a questionnaire instrument. Questionnaires have been prepared based on indicators of each variable by using Likert’s scale. The result of descriptive analysis showed that Indonesian people accepted internet television services using the modification technology acceptance model approach. The result of CB-SEM showed the model of internet television is quite fit and the hypothesis indicate that perceived usefulness, perceived enjoyment, perceived quality has influence toward intention through attitude in simultaneously and partial.